(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
ABSTRACT- From the beginning, binders such as red mud mortar, lime mortar, cement mortar, etc., played a major role. It has been found that the production of cement increases the quantity of uncontrollable CO2 emissions. Another adhesive that can be used in place of cement is geopolymer. Because geopolymer concrete may reduce carbon emissions, the concrete business could grow sustainably and prosper as a result. This technology has the potential to reduce CO2 emissions from the construction sector by up to 80%. To make the binder for geo polymer concrete, alkaline solutions are used to activate sources of materials rich in silica (Si) and aluminium (Al), such as fly ash, GGBS, etc. Geopolymer-made concrete includes no cement at all. In this study, we attempted to determine the compressive strength and durability properties of geopolymer concrete using various molarities of 8M, 10M, and 12M along with Sodium Silicate solution. The alkaline activators used were Sodium hydroxide (NaOH), Potassium hydroxide (KOH), and combination of both (50%NaOH + 50%KOH). To achieve the highest pH value for better mechanical and durability characteristics, chemical analysis is done. After 7 and 28 days of age, the Compression and Permeability experiments were conducted. The GPC’s strength and durability characteristics were contrasted with those of conventional concrete.